Physico-chemical changes during growth and development of grapefruits (Citrus paradisi Macf.). I. Physical changes - Mohammed Almahi, Ali Azhari; Abu-Goukh, Abu-Bakr Ali (Gezira Journal of Agricultural Science; Vol 15 No 1 (2017), 2017)
The physical changes during growth and development of seedy pinkfleshed ‘Red Blush’ grapefruits were evaluated, to provide base-line information regarding the biochemistry of the developing fruit and to assist in determining harvest maturity of grapefruits. The fruits followed a typical single sigmoid growth curve. Fruit fresh weight, volume, length, diameter, peel thickness, pulp diameter, juice content, and peel color progressively increased from 4 weeks after anthesis (WAA) up to 26 WAA at physiological maturity and then remained constant. Respiration rate exhibited a typical non-climacteric pattern. It decreased from 239.8 mg CO 2 /kg-hr (4 WAA) to 21.1 mg CO 2 /kg-hr (26 WAA). Peel/pulp ratio and fruit flesh firmness steadily decreased with advancement in growth and development, reaching minimum values at physiological maturity. Grapefruits should be harvested at least at physiological maturity, where the fruit attains maximum size and weight, juice content at maximum level, peel/pulp ratio at minimum, rind color develops, and it is still firm.     قومت التغيرات الفيزيائية أثناء النمو والتطور لثمار القريب فروت أحمر اللب ذي البذور من الصنف "رد بلش"، وذلك لتوفير المعلومات الأساسية المتعلقة بكيمياء الثمار أثناء تطورها لتساعد في تحديد مرحلة اكتمال النمو لثمار القريب فروت. اتبعت ثمار القريب فروت في نموها نمط منحنى النمو المنفرد. زادت الثمار في الوزن الطري والحجم والطول وقطر الثمرة و سمك القشرة وقطر اللب وكمية العصير ولون القشرة زيادة مضطردة من أربعة أسابيع بعد تفتح الأزهار إلى 26 أسبوعاً بعد تفتح الأزهار عند مرحلة اكتمال النمو الفسيولوجي، وثبتت في مقاديرها بعد ذلك. تبع معدل تنفس الثمار نمط التنفس غير الكلايماكتيرى، حيث انخفض من 239.8  ملجم ثاني أكسيد الكربون/ كجم- ساعة (4 أسابيع بعد تفتح الأزهار) إلى 21.1 ملجم ثاني أوكسيد الكربون/ كجم- ساعة (26 اسبوعاٌ بعد تفتح الأزهار). انخفضت نسبة القشرة إلى اللب وصلابة لب الثمار على الدوام مع تقدم الثمار في مراحل النمو والتطور. لذلك يجب حصاد ثمار القريب فروت عند مرحلة اكتمال النمو الفسيولوجي، على الأقل، حيث تكون الثمرة قد بلغت الحجم والوزن النهائي، وكمية العصير في أعلى مستوياتها، ونسبة القشرة لللب في أدنى حدودها، والقشرة قد تلونت، وتكون الثمرة ما زالت صلبة القوام.